From Cooper-pair glass to unconventional superconductivity: a unified approach to cuprates and pnictides. (May 2017) - Sacks, William; Mauger, Alain; Noat, Yves
Abstract: We report a microscopic model wherein the unconventional superconductivity emerges from an incoherent 'Cooper-pair glass' state. Driven by the pair-pair interaction, a new type of quasi-Bose phase transition is at work. The interaction leads to the unconventional coupling of the quasiparticles to excited pair states, or 'super-quasiparticles', with a non-retarded energy-dependent gap. The model describes quantitatively the quasiparticle excitation spectra of both cuprates and pnictides, including the universal 'peak-dip-hump' signatures, and for the pseudogap phase above T c . The results show that instantaneous pair-pair interactions account for the SC condensation without a collective mode. Abstract : Highlights: Understanding high-Tc superconductivity in cuprates and pnictides is among the outstanding problems in condensed matter today. In this letter, we address two key questions: are there preformed pairs above Tc? What is the origin of the dip singularity in the excitation spectra? We propose a microscopic theory which explains the pseudogap state and gives the precise shape of the spectra in both classes of materials. These results should interest experts in the field but also a wider readership of both experimentalists and theoreticians of condensed matter.